Application of the Think-Talk-Write Model of Cooperative Learning for Improving Paragraph Writing Abilities - Nihlah, Nihlah; Meilana, Septi Fitri (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
The purpose of this study was to analyze the ability of paragraph writing abilities by using the Think-Talk-Write Model of cooperative learning in IV graders of MI Darul Ma'arif, Tangerang City. The descriptive-qualitative study was conducted at MI Darul Ma'arif Tangerang City to achieve this objective. The data in this study were in the form of the application of the Think-Talk-Write Model of Cooperative Learning, the ability to write paragraphs, and data sources (Indonesian language teachers and fourth-grade students of MI Darul Ma'arif). Data collection techniques were carried out through interviews and documentation. Data analysis techniques included data reduction through the application of the Think-Talk-Write Model of Cooperative Learning and paragraph writing abilities. Data presentation, critically analyzing the data presented with relevant theories and juxtaposing it with several related studies, conclusion drawing, and verification. The results showed that the fourth-grade students of Madrasah Ibtidaiyah Darul Ma'arif, Tangerang City, had diverse potential, namely 62% of students in the good category and 38% of students in the bad category, in making free essays focused on paragraph writing abilities. Based on the data analysis, it can be concluded that the paragraph text written by fourth-grade students of MI Darul Ma'arif still needs development in terms of learning models, self-motivation, the surrounding environment, and the teacher's ability to provide teaching to students. The importance of good cooperation between teachers and parents.